Bird conservation and the land sharing‐sparing continuum in farmland‐dominated landscapes of lowland England. Issue 5 (9th April 2019) - Finch, Tom; Gillings, Simon; Green, Rhys E.; Massimino, Dario; Peach, Will J.; Balmford, Andrew
Abstract: Empirical evidence from many regions suggests that most species would be least negatively affected if human food demand were met through high‐yield agricultural production and conservation of nonfarm ecosystems (land sparing), rather than through wildlife‐friendly farming over a larger area (land sharing). However, repeated glaciation and a long history of agriculture may lead to different results in regions such as western Europe. We compared the consequences of land sparing and land sharing on breeding bird species in 2 lowland regions of England, The Fens, with 101 species, and Salisbury Plain, with 83. We derived density–yield responses for each species and then estimated regional population size under regional food production strategies, including land sharing and land sparing, a range of intermediate strategies, and a novel mixed strategy. In both regions, more species achieved maximum regional population size under land sparing than land sharing. In The Fens, the majority of birds were loser species (estimated to have smaller populations under all food production strategies than in the preagricultural baseline scenario), whereas in Salisbury Plain the majority were winners (smaller populations in the preagricultural baseline scenario). Loser species overwhelmingly achieved maximum regional population size under land sparing, whereas winner species achieved maximum regional population size under either land sharing or an intermediate strategy, highlighting the importance of defining which groups of species are the target of conservation. A novel 3‐compartment strategy (combining high‐yield farming, natural habitat, and low‐yield farming) often performed better than either land sharing or land sparing. Our results support intermediate or 3‐compartment land‐sparing strategies to maximize bird populations across lowland agricultural landscapes. To deliver conservation outcomes, any shift toward land sparing must, however, ensure yield increases are sustainable in the long term, do not entail increased negative effects on surrounding areas, and are linked to allocation of land for nature. Abstract : Article impact statement : By freeing up land for conservation, high‐yield farming can maximize biodiversity outcomes even in long‐converted landscapes. Abstract : Conservación de Aves y el Continuo de Suelo Compartido‐Reservado en Paisajes Dominados por Tierras de Cultivo en las Tierras Bajas de Inglaterra Resumen: La evidencia empírica proveniente de muchas regiones sugiere que la mayoría de las especies se verían menos afectadas negativamente si se cumpliera con la demanda humana de alimentos por medio de una producción agrícola de alto rendimiento y la conservación de ecosistemas no agrícolas (dosificación de suelo) en lugar de hacerlo a través de la agricultura amigable con la fauna en un área mayor (partición de suelo). Sin embargo, la glaciación repetitiva y una larga historia agrícola podrían brindar diferentes resultados en regiones como Europa occidental. Comparamos las consecuencias de la dosificación y la partición de suelo sobre especies de aves en reproducción en dos regiones de tierras bajas en Inglaterra: Los Fens, con 101 especies, y la Planicie Salisbury, con 83 especies. Derivamos las respuestas con densidad de rendimiento para cada especie y después estimamos el tamaño poblacional regional bajo estrategias regionales de producción de alimentos, incluyendo la dosificación y la partición de suelo, una gama de estrategias intermedias y una novedosa estrategia mixta. En ambas regiones, más especies alcanzaron el tamaño poblacional máximo para la región bajo la dosificación del suelo que bajo la partición del suelo. En Los Fens, la mayoría de las aves fueron especies perdedoras (se estimó que tendrían tamaños poblacionales menores bajo todas las estrategias de producción de alimento que en el escenario pre‐agrícola de la línea base) mientras que en la Planicie Salisbury, la mayoría de las especies fueron ganadoras (con poblaciones más pequeñas en el escenario pre‐agrícola de la línea base). Las especies perdedoras tuvieron abrumadoramente un tamaño poblacional máximo para la región bajo la dosificación de suelo, mientras que las especies ganadoras tuvieron este máximo poblacional bajo la partición de suelo o alguna estrategia intermedia, lo que resalta la importancia de la definición de cuáles grupos de especies son el objetivo de conservación. Una estrategia novedosa de tres compartimentos (combina la agricultura de alto rendimiento, el hábitat natural y la agricultura de bajo rendimiento) muchas veces tuvo un mejor desempeño que la dosificación o la partición del suelo. Nuestros resultados respaldan a las estrategias de dosificación de suelo intermedias o de tres compartimentos para maximizar las poblaciones de aves en todos los paisajes agrícolas de las tierras bajas. Para brindar resultados de conservación, cualquier cambio hacia la dosificación del suelo, sin embargo, debe asegurar que los incrementos en el rendimiento son sustentables a largo plazo, no conllevan un incremento de efectos negativos en las áreas circundantes, y que están vinculados a la asignación de suelo para la naturaleza. 摘要: 来自许多地区的经验证据表明, 如果人类通过高产农业和保护非农业生态系统的方式 (土地分离) 来满足粮食需求, 而不是通过在较大范围内开展野生动物友好型农业 (土地共享), 那么大多数物种受到的负面影响会是最小的。然而, 一些地区 (如西欧) 经历过多次冰川作用, 且有着悠久的农业历史, 可能在这个问题上有所不同。我们比较了英国两个低地地区土地分离和土地共享对繁殖鸟类的影响, 其中东部沼泽地区 (The Fens) 有 101 种鸟, 索尔斯堡平原 (Salisbury Plain) 有 83 种鸟。我们估计了每个物种的密度‐产量响应关系, 并评估了各种区域粮食生产策略下鸟类的区域种群大小, 这些策略包括土地分离、土地共享、一系列中间型策略以及一种新型混合策略。在这两个地区, 较多物种在土地分离策略 (而不是土地共享策略) 下的区域种群大小最大。在沼泽地区, 大部分鸟类物种属于失败者 (据估计, 它们在任何粮食生产策略下的种群数量都低于未发展农业时的基线水平); 而索尔斯堡平原的大多数鸟类物种都是成功者 (未发展农业时的基线水平更低) 。失败物种绝大多数都在土地分离策略下可以达到最大区域种群数量, 而成功物种则会在土地共享或中间型策略下达到最大区域种群数量。这一结果突显了确定保护目标中鸟类类型的重要性。此外, 还存在一种新型的三区分隔策略 (结合了高产农业、自然生境和低产农业), 它的效果往往比单一的土地分离或土地共享更好。我们的结果支持选择中间型或三区分隔型土地分离策略, 以求在低地农业景观中使鸟类种群数量最大化。然而, 要取得保护成效, 还应确保在向土地分离策略的转型中, 产量的增长可长期持续、不会为周围地区带来更多负面影响, 且与自然用地的分配相关联。【翻译: 胡怡思; 审校: 聂永刚】